2019
DOI: 10.1016/j.medengphy.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Patellar tendon buckling in post-operative total knee arthroplasty patients is more prominent than in healthy controls

Abstract: Recent evidence suggests the patellar tendon undergoes buckling during normal knee flexion, which likely contributes to the functioning of the extensor mechanism. Thus, evaluating buckling in patients following total knee arthroplasty (TKA), where extensor mechanism dysfunction remains a common complication, may be relevant. The study goals were to identify whether post-TKA patients exhibit differences in patellar tendon buckling from healthy, similarly-aged adults and whether such buckling correlates with kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A study by Slane et al 45 demonstrated an increase in patellar tendon buckling in post-TKR patients compared to the control. These patients also exhibited larger buckling angle, magnitude, and amplitude.…”
Section: Instabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…A study by Slane et al 45 demonstrated an increase in patellar tendon buckling in post-TKR patients compared to the control. These patients also exhibited larger buckling angle, magnitude, and amplitude.…”
Section: Instabilitymentioning
confidence: 97%
“… 46 48 Factors to consider are that patients with OA might already have differences in patellar tendon buckling as OA leads to weakness in the quadriceps due to the anatomical function of the patellar tendon as part of a muscle unit. 45 , 49 …”
Section: Instabilitymentioning
confidence: 99%